Analisis Pendapatan Padi Sawah Di Desa Jojog Kecamatan Pekalongan Kabupaten Lampung Timur - Sari, Dwi Maya; Trisnanto, Teguh Budi; Apriyani, Marlinda; Sutarni, Sutarni (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Rice is an important and staple commodity for the food consumption of the Indonesian people. Lowland rice production in East Lampung Regency is in second place with 466,563.66 tons after Central Lampung with 555,127.87 tons. In 2020 the fifth largest rice production in East Lampung Regency is Pekalongan District with 37,789 tons and has a harvested area of 6,910 ha. The agricultural area in Jojog Village is the highest compared to other villages in Pekalongan District. However, this area of land is not proportional to the amount of harvest produced and the income of farmers. The purpose of writing this final project is to analyze the income of paddy rice farming in Jojog Village. The determination of the sample in this final project uses a non-probability sampling technique, which is a data collection technique or sample so that all data is likely to be selected as a sample that is not the same size, using a purposive sampling technique, namely by deliberately determining respondents consisting of 60 farmers, namely 30 respondents rice farming established variety and 30 respondents rice farming impari variety 32. The analytical method used is the analysis of farm income. The results showed that the average production of established variety rice was 2,647 kg/farmer or 7,058 kg/ha with a selling price of IDR 4300/kg, while for the impari 32 variety 2,372 kg/farmer or 6,777 kg/ha with a selling price of IDR 4300/kg obtained an average income of rice farming of the impari 32 variety of IDR 5,664,603/farmer or IDR 16,184,581/ha. The R/C ratio value of the established variety was 2.23 and the B/C ratio was 1.23, while the R/C ratio value for the impari 32 variety was 2.25 and the B/C ratio was 2.25 indicating that lowland rice farming in Jojog village is profitable.